2009
DOI: 10.1371/journal.pntd.0000387
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ecto-Nucleoside Triphosphate Diphosphohydrolase Activity on Trypanosoma cruzi Infectivity and Virulence

Abstract: BackgroundThe protozoan Trypanosoma cruzi is the causative agent of Chagas disease. There are no vaccines or effective treatment, especially in the chronic phase when most patients are diagnosed. There is a clear necessity to develop new drugs and strategies for the control and treatment of Chagas disease. Recent papers have suggested the ecto-nucleotidases (from CD39 family) from pathogenic agents as important virulence factors. In this study we evaluated the influence of Ecto-Nucleoside-Triphosphate-Diphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
0
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(122 citation statements)
references
References 43 publications
(55 reference statements)
8
103
0
11
Order By: Relevance
“…In this sense, the ecto-nucleoside-triphosphate-diphosphohydrolase, homolog to CD39 family enzymes, is localized on the external surface of all biological stages of T. cruzi, and it has been proposed as new chemotherapy target to block the infection (47). Moreover, the infective form (trypomastigote) presents the highest ATP hydrolysis rate, and its enzymatic activity increases in vitro cell infection and parasitemia in a murine model of Chagas disease (47). However, there are no reports about the effect of APCP in parasite ectonucleotidases.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the ecto-nucleoside-triphosphate-diphosphohydrolase, homolog to CD39 family enzymes, is localized on the external surface of all biological stages of T. cruzi, and it has been proposed as new chemotherapy target to block the infection (47). Moreover, the infective form (trypomastigote) presents the highest ATP hydrolysis rate, and its enzymatic activity increases in vitro cell infection and parasitemia in a murine model of Chagas disease (47). However, there are no reports about the effect of APCP in parasite ectonucleotidases.…”
Section: Discussionmentioning
confidence: 99%
“…The GP63, a zinc-metalloprotease named glycoprotein 63 (GP63), is another critical virulence factor that has been fully explored [34][35][36][37][38] . However, the E-NTPDases (ecto-nucleoside triphosphate diphosphohydrolases), while less-extensively studied, have been demonstrated and believed to be important infectivity and virulence factors [39][40][41][42][43][44][45][46][47][48] .…”
Section: Leishmania Braziliensis Is Responsible For Most Cases Of MLmentioning
confidence: 99%
“…All those mediators are highly toxic to T. cruzi 18 . It has been described that Tc-ENTPDase-1 might play a modulatory role in response to these toxic mediators and in consequence affect purine recovery pathways, which are necessary for nutrition and to maintain parasite viability; beyond this, they can be involved in inflammatory processes, modulation of the host immune system and consequently increase the virulence mechanisms of T. cruzi 17,19,20 . A virulence key mechanism related to Tc-ENTPDase-1 presents a relation with enzyme capacity that interferes with extracellular ATP signals and interrupts purinergic signalling, limiting mechanisms of host defences.…”
Section: All Authors Contributed To Conception and Design Manuscriptmentioning
confidence: 99%
“…Trypanocidal drugs that are able to influence the biochemical activity of purinergic receptors, acting like competitive antagonists of P2X and P2Y receptors, may be promising in the clinical management of Chagas disease 24 . It has been shown that there is a strong correlation of ecto-ATPase activity inhibition with reduced capacity of adhesion and internalisation of T. cruzi in the host cell 17,20 . An important ecto-ATPase inhibitor, capable of interfering with purinergic receptors and consequently in the biology of T. cruzi, is suramin, a polysulphonated naphthylurea compound, derivative of urea, that functions as a competitive antagonist of P2 receptors, used for the prophylactic treatment of African tripassonomiase 25 .…”
Section: All Authors Contributed To Conception and Design Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation